Fluorescent Carbon Dots Capped with PEG(200) and Mercaptosuccinic Acid - Helena Goncalves (2010)
The synthesis and functionalization of carbon nanoparticles with PEG(200) and mercaptosuccinic acid, rendering fluorescent carbon dots, is described. Fluorescent carbon dots (maximum excitation and emission at 320 and 430 nm, respectively) with average dimension 267 nm were obtained. The lifetime decay of the functionalized carbon dots is complex and a three component decay time model originated a good fit with the following lifetimes: tau (1) = 2.71 ns; tau (2) = 7.36 ns; tau (3) = 0.38 ns. The fluorescence intensity of the carbon dots is affected by the solvent, pH (apparent pK (a) of 7.4 +/- 0.2) and iodide (Stern-Volmer constant of 78 +/- 2 M-1).